The dynamic shape changes of the tongue base during respiration, chewing and swallowing - Doris Haydee Rosero Salazar; Zi-Jun Liu; Amy Ly; Yikang Dong; Alexander Veasna Simnhoung (PLoS ONE, 2025)
This study aimed to analyze dimensional deformations of the tongue base during respiration, chewing, and swallowing. Eight 7–8-month-old Yucatan minipigs were used. Under deep sedation, eight 2mm ultrasonic piezoelectric (SONO) crystals were implanted in the tongue base forming a cubic-shaped configuration, representing right/left dorsal and ventral lengths, anterior/posterior dorsal and ventral widths, and right/left anterior and posterior thicknesses. Next, 8 pairs of electromyographic (EMG) microelectrodes were inserted into the tongue, jaw, hyoid, pharyngeal, and palatal muscles. SONO and EMG signals during respiration were recorded. Then, minipigs were allowed to wake-up for unrestrained feeding. The feeding sessions were recorded with synchronized EMG and videofluoroscopy to confirm the phases of jaw movement in chewing, and swallowing episodes. Amplitudes, durations, and timings for each dimension of the SONO crystal-circumscribed region were measured from the start of the jaw opening. Findings during respiration showed elongated lengths, anterior widths and anterior thickness (p<0.05). For chewing, the width elongated up to 17% while the length and thickness shortened (12–33% and 10–32% respectively, p<0.05). Onsets of deformational changes in length and thickness occurred 10–30% earlier than in width. The cycle duration was 0.55 ± 0.11seconds chewing, and 0.69 ± 0.16seconds swallowing. During swallowing, the dorsal length (5–12%) and posterior width (10–14%) elongated whereas the posterior thickness (9–15%) and ventral length (4–10%) shortened. Explicit 3D-kinematic patterns in relation to specific functions characterize the tongue base deformation. The findings of this analysis will contribute to a better understanding of the oropharyngeal biomechanics upon abnormal conditions.